Promosi Ikatan Sosial Berkelanjutan berdasarkan Perspektif Konstitusi Indonesia - Indriastuty, Dwi Elok; Fithri, Nur Hidayatul (Law and Human Rights Policy Strategy Agency, Ministry of Law and Human Rights of The Repub, 2024)
Social bonds are one of the types of bonds based on available themes regulated in POJK No 18 of 2023. The drafting of POJK 18/2023 did not consider regulations from either a theoretical or constitutional perspective, which should be the main consideration for any legislative regulation. This article is the result of research aimed at finding arguments and constitutional rationality related to the regulation of social bonds, sustainable bonds, and sustainability-related bonds. As a result, research on the constitutional analysis of Indonesia's social securities regulation becomes highly important, considering that the constitution serves as the source of legitimacy or the foundation of `authorization for laws and regulations beneath it. According to universal legal principles, laws and regulations that are subordinate to the constitution must not contradict higher laws This is where the concept of legal hierarchy and regulations becomes necessary, so that regulations do not conflict with those above them in the hierarchy, including the highest point, which is the constitution. The research method used in this study is normative exploratory legal research with a constitutional approach and a conceptual approach. It is clear that this article will closely examine several areas of social bond regulation from the perspective of the Indonesian Constitution .The research findings reveal juridical arguments and rationality that, as a welfare-oriented state in its constitution and born from its collectivist cultural background, social bond regulation aligns with the principles of the constitution applicable in Indonesia.